O estágio docência na formação de professores da Educação Superior: representações de estudantes do mestrado em Saúde Coletiva - Freitas, Elci Nilma Bastos (2016)
This text, written during a research developed in the Graduate Program in Education at the UnivesidadeEstadual de Feira de Santana - Bahia, aims to understandthe contribution of the Teaching Internship for pedagogic training of teachers of Higher Educationthrough the representations of students of the Community Health Master. It was certified that the curricular component Teaching Internship is an important education environment of the future university professor, locus in which students of the Graduate Program strictosensuacquire some of the knowledge needed for teaching practice. However, it is worth noting that teaching learning extends throughout one’s whole career. To achieve the established objective, we conducted a descriptive qualitative research, which was based on principles of the Social Representations Theory – SRT (MOSCOVICI, 2003a, 2003b; JODELET, 1989, 2001 e 2007). Regarding the production of data, it was held a documentary analysis(TRIVIÑOS, 1987) of the regiment and of the pedagogic proposal of the Graduate Community Health Program at UEFS. It was also used semi structured interviews (MINAYO, 2006), which were carried out with 12 students from the Academic Master of the aforementioned Program. In order to analyze the data produced in the research some principles of Content Analysis(BARDIN, 2011) were used. In the discussion of the data produced five categories were identified, as follows: the first refers to the concept of teaching internship; in the second, the knowledge necessary for university teaching is discussed; in the third was verified which were the contributions of the internship to university teaching; in the fourth the process of the Teaching Internship experience was described and, finally, in the fifth category, where suggestions to improve the experience of Teaching Internship were presented by our contributors. The main conclusions of this research focus that the internship contributes to the preparation of graduate students for university teaching and for the development of teacher identity. Moreover, it contributes to this preparation for the acquisition of knowledge of the reality of university classroom, for the exchange of knowledge with the experienced teacher and, finally, for the perception of the master students on the human condition of the teaching profession and the humanization in the relationships that occur in the educational context.In addition to these contributions, our contributors address the need for the Community Health Program not prioritizing specific studies and research training at the expense of teacher training, given the complexity of teaching today, which requires special attention.Participants also emphasized the prevalence of the following difficulties during the Teaching Internship experience: the absence of an effective interaction between the Undergraduate and Graduate programs, structural and political problems that damaged the internship. In addition to this, the students had difficulties in understanding the importance of courses in their training, didactic and pedagogical difficulties of interns to conduct the courses and embarrassments of master students to assess and deal with the graduate students taking the course again after failing. Furthermore, our study confirmed the need to implement institutional policies for the formation of the university teacher, especially with beginning teachers who are in a period of adaptation and professional learning and also with experienced teachers to reflect on their teachingpractices continuously so they can update and innovate their practices.